Full-Wave Simulation of a Helmholtz Radiofrequency Coil for Magnetic Resonance Applications - Giulio Giovannetti; Denis Burov; Angelo Galante; Francesca Frijia (Technologies)
Magnetic resonance imaging (MRI) is a non-invasive diagnostic technique able to provide information about the anatomical, structural, and functional properties of different organs. A magnetic resonance (MR) scanner employs radiofrequency (RF) coils to generate a magnetic field to excite the nuclei in the sample (transmit coil) and pick up the signals emitted by the nuclei (receive coil). To avoid trial-and-error approaches and optimize the RF coil performance for a given application, accurate design and simulation processes must be performed. We describe the full-wave simulation of a Helmholtz coil for high-field MRI performed with the finite-difference time-domain (FDTD) method, investigating magnetic field pattern differences between loaded and unloaded conditions. Moreover, the self-inductance of the single loops constituting the Helmholtz coil was estimated, as well as the frequency splitting between loops due to inductive coupling and the sample-induced resistance. The result accuracy was verified with data acquired with a Helmholtz prototype for small phantom experiments with a 3T MR clinical scanner. Finally, the magnetic field variations and coil detuning after the insertion of the RF shield were evaluated.